Christian attitudes towards the bible through wikipedia content - Yousef A. Baker, El-Ebiary; Allaa, EddinIsmaail; Mohammed Elsayed Mohammed, MohammedAbdou (The Mattingley Publishing Co., Inc., 2020)
In the era of informatics, the proliferation of many electronic encyclopaedias with which conflicting sources and opinions. This research focuses on a well-known electronic encyclopaedia, which is Wikipedia, and looking at the content in it regarding the theoretical research sample. Also this research discusses a very important topic in theological studies namely the position of Christian sects and early church fathers on the Gospels as there is no consensus regarding this issue, contrary to common belief among the non-specialists. For instance, the Catholic church belief on the Gospels is differs from that of the Protestant church. The research surveys the position of the Catholic, Protestant and Orthodox churches and some of their denominations on this topic. Furthermore, the article examines the opinion of the church fathers who are considered holy by Christians of all sects, among others are Irenaeus, Origen, Eusebius of Caesarea, Clement of Rome, Clement of Alexandria, Marcion and Cyril of Jerusalem from Christian sources. This paper concludes that the differences regarding the Gospels among the sects and the church fathers are very significant.